2021
DOI: 10.3390/nu13093289
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Type 2 Diabetes Associations with the Gut Microbiome in Individuals from Two Ethnic Backgrounds Living in the Same Geographic Area

Abstract: It is currently unknown whether associations between gut microbiota composition and type 2 diabetes (T2D) differ according to the ethnic background of individuals. Thus, we studied these associations in participants from two ethnicities characterized by a high T2D prevalence and living in the same geographical area, using the Healthy Life In Urban Settings (HELIUS) study. We included 111 and 128 T2D participants on metformin (Met-T2D), 78 and 49 treatment-naïve T2D (TN-T2D) participants, as well as a 1:1 match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…The microbial features that potentially mediate these differences included 25 species and 27 pathways that are significantly (FDR-corrected linear-mixed model p < 0.05) differentially abundant between the two subsets (Table S7). Pathways related to menaquinol biosynthesis, previously associated with type 1 (Roth-Schulze et al, 2021) and type 2 diabetes (Balvers et al, 2021;Dash and Bataineh, 2021;Wu et al, 2020), were the most overrepresented features in mouse recipients of baseline microbiomes from top responders (p = 0.0006, Figure 7F). Pathways related to purine (p < 0.0001) and pyrimidine (p = 0.005) biosynthesis were more abundant in mouse recipients of baseline microbiomes of top responders, whereas purine degradation (p < 0.0001) was more abundant in recipients of baseline microbiomes from bottom responders (Figure 7F), in line with the correlation between purine biosynthesis and elevated glycemic response noted in the entire sucralose group (Figure 4A).…”
Section: Causative Personalized Impacts Of Nns-modulated Microbiome O...mentioning
confidence: 72%
“…The microbial features that potentially mediate these differences included 25 species and 27 pathways that are significantly (FDR-corrected linear-mixed model p < 0.05) differentially abundant between the two subsets (Table S7). Pathways related to menaquinol biosynthesis, previously associated with type 1 (Roth-Schulze et al, 2021) and type 2 diabetes (Balvers et al, 2021;Dash and Bataineh, 2021;Wu et al, 2020), were the most overrepresented features in mouse recipients of baseline microbiomes from top responders (p = 0.0006, Figure 7F). Pathways related to purine (p < 0.0001) and pyrimidine (p = 0.005) biosynthesis were more abundant in mouse recipients of baseline microbiomes of top responders, whereas purine degradation (p < 0.0001) was more abundant in recipients of baseline microbiomes from bottom responders (Figure 7F), in line with the correlation between purine biosynthesis and elevated glycemic response noted in the entire sucralose group (Figure 4A).…”
Section: Causative Personalized Impacts Of Nns-modulated Microbiome O...mentioning
confidence: 72%
“…Agathobaculum butyriciproducens is a strictly anaerobic and butyric acid-producing bacteria that has had impressive success in restoring cognition in Alzheimer's disease mouse models ( 29 ). Anaerostipes hadrus can produce butyrate from carbohydrates or lactate ( 30 , 31 ) and is often decreased in diabetes ( 32 ). Eubacterium rectale is also a butyrate producer ( 33 ) responsible for metabolizing dietary plant polysaccharides ( 34 ); it is increased in obesity ( 35 ) and reduces inflammatory dendritic cells ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both clinical and basic studies have confirmed that some patients with UC and UC mouse models induced by DSS decrease gut microbiota diversity ( Xu et al., 2021a ; Zhuang et al., 2021 ), and after exclusive enteral nutrition and chemical drug treatment, α-diversity indicators show an upward trend ( Radhakrishnan et al., 2022 ). Similarly, decreased diversity has been observed in individuals with T2DM and in high-fat-fed mouse models ( Nyavor et al., 2019 ; Balvers et al., 2021 ). As described in Tables 1 , 2 , most TCMs, such as curcumin and Rhizoma atractylodis macrocephalae , restore the diversity of flora, which may be one of the factors for treating different diseases using the same method.…”
Section: Discussionmentioning
confidence: 81%